MicroRNA-21 (miR-21) regulates cellular proliferation, invasion, migration, and apoptosis by targeting PTEN, RECK and Bcl-2 in lung squamous carcinoma, Gejiu City, China. - Long-Feng Xu (Public Library of Science (PLoS), 2014)
Background In South China (Gejiu City, Yunnan Province), lung cancer incidence and associated mortality rate is the most prevalent and observed forms of cancer. Lung cancer in this area is called Gejiu squamous cell lung carcinoma (GSQCLC). Research has demonstrated that overexpression of miR-21 occurs in many cancers. However, the unique relationship between miR-21 and its target genes in GSQCLC has never been investigated. The molecular mechanism involved in GSQCLC must be compared to other non-small cell lung cancers in order to establish a relation and identify potential therapeutic targets. Methodology/principal findings In the current study, we initially found overexpression of miR-21 occurring in non-small cell lung cancer (NSCLC) cell lines when compared to the immortalized lung epithelial cell line BEAS-2B. We also demonstrated that high expression of miR-21 could increase tumor cell proliferation, invasion, viability, and migration in GSQCLC cell line (YTMLC-90) and NSCLC cell line (NCI-H157). Additionally, our results revealed that miR-21 could suppress YTMLC-90 and NCI-H157 cell apoptosis through arresting cell-cycle at G2/M phase. Furthermore, we demonstrated that PTEN, RECK and Bcl-2 are common target genes of miR-21 in NSCLC. Finally, our studies showed that down-regulation of miR-21 could lead to a significant increase in PTEN and RECK and decrease in Bcl-2 at the mRNA and protein level in YTMLC-90 and NCI-H157 cell lines. However, we have not observed any remarkable difference in the levels of miR-21 and its targets in YTMLC-90 cells when compared with NCI-H157 cells. Conclusions/significance miR-21 simultaneously regulates multiple programs that enhance cell proliferation, apoptosis and tumor invasiveness by targeting PTEN, RECK and Bcl-2 in GSQCLC. Our results demonstrated that miR-21 may play a vital role in tumorigenesis and progression of lung squamous cell carcinoma and suppression of miR-21 may be a novel approach for the treatment of lung squamous cell carcinoma.